Effect of heat input and weld chemistry on mechanical and microstructural aspects of double side welded austenitic stainless steel 321 grade using tungsten inert gas arc welding process. Issue 3 (17th March 2020) - Mohan Kumar, S.; Siva Shanmugam, N.
Abstract: Stainless steel 321 is a stabilized austenitic grade that prevents the formation of chromium carbides at the grain boundaries and subsequently reduces the risk of corrosion attack at the weld surface by forming titanium carbide. It is primarily used in industries such as pressure vessels, boilers, nuclear reactors, carburetors and car exhaust systems. In order to assess the effect of gas tungsten arc welding process parameters on weld penetration, the proposed Taguchi L9 orthogonal matrix has been selected with two factors and three levels for welding austenitic stainless steel 321 by adjusting the welding current and welding speed. Bead‐on‐plate experiments were performed on base metal of 6 mm thick plate by changing the process parameters, and corresponding weld bead measurement and macrostructure images are examined. Maximum depth of penetration −3.3017 mm is achieved with a heat input −1.4058 kJ/mm, i. e., welding current‐220 A and welding speed‐120 mm/min. Double‐side arc welding technique is used to obtain full penetration on 6 mm thick plate. The quality of the weldment was assessed using non‐destructive radiography inspection. Mechanical integrity and microstructural characteristics of the weldments were studied using tensile (transverse and longitudinal), bend, impact, microhardness, optical microscopy, energy dispersive x‐ray spectroscopy, x‐ray diffraction analysis, ferrite number measurement and scanning electron microscope. The results reveal that the double side‐tungsten inert gas weldment have better mechanical properties. It is corroborated from the weld metal microstructure that it contains γ ‐austenite, δ‐ferrite and titanium carbides (intermetallic compounds). X‐ray diffraction analysis and energy dispersive x‐ray spectroscopy plots confirm the increase in the ferrite phase in weld metal. The ferrite measurement results show that the ferrite volume in the base metal and weld metal is 1.2 percent and 6.1 percent respectively. In addition, the higher δ‐ferrite volume in the weldment helps in attaining superior mechanical integrity. Fractography shows that the failure mode of the weld metal and the base metal is ductile. Abstract : The welded joint showed enhanced mechanical properties compared to base metal. At room temperature, the double side‐arc welded samples had higher notched tensile strength than the parent metal. This could be corroborated to the phenomenon that double‐side arc welds had dense and equiaxed dendrites and more austenite's were deformed during the tensile tests. The weld metal microstructure characterized by columnar dendrites, equiaxed dendrites and titanium carbides.